Which neurodevelopmental processes continue in humans after birth? - Sorrells, Shawn Fletcher (Frontiers in Neuroscience, 2024)
Once we are born, the number and location of nerve cells in most parts of the brain remain unchanged. These types of structural changes are therefore a significant form of flexibility for the neural circuits where they occur. In humans, the postnatal birth of neurons is limited; however, neurons do continue to migrate into some brain regions throughout infancy and even into adolescence. In human infants, multiple migratory pathways deliver interneurons to destinations across the frontal and temporal lobe cortex. Shorter-range migration of excitatory neurons also appears to continue during adolescence, particularly near the amygdala paralaminar nucleus, a region that follows a delayed trajectory of growth from infancy to adulthood. The significance of the timing for when different brain regions recruit new neurons through these methods is unknown; however, both processes of protracted migration and maturation are prominent in humans. Mechanisms like these that reconfigure neuronal circuits are a substrate for critical periods of plasticity and could contribute to distinctive circuit functionality in human brains.